Autonome Shuttlebusse Im ÖPNV 2019
DOI: 10.1007/978-3-662-59406-3_9
|View full text |Cite
|
Sign up to set email alerts
|

Empirische Beobachtungen zur Akzeptanz des Pilotprojektes „Autonom fahrender Kleinbus“ unter den Bürger∗innen von Bad Birnbach

Abstract: In dem Beitrag werden auf der Grundlage einer Haushaltsbefragung in Bad Birnbach Aussagen zur Akzeptanz, Aufgeschlossenheit und Bewertung gegenüber dem Pilotprojekt getroffen. Die Wahrnehmung und Bewertung von Eigenschaften des automatisiert fahrenden Kleinbusses wie auch Präferenzen, Werte sowie Einstellungen von Anwohnern zu autonom fahrenden Fahrzeugen sind dabei von Interesse. Als Analyseschema wird eine Einteilung nach den Akzeptanzdimensionen der Einstellungs-, Handlungs-und Nutzungsebene verwendet. Das … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
0
0
1
Order By: Relevance
“…Even for the non-users of the EVA Shuttle, the survey revealed a general open-mindedness towards the future use of an autonomous minibus. In contrast to the minibus service in Trikala (see Portouli et al [35]), but in line with most other studies, such as Rauh et al [36], the main reason for using the EVA Shuttle was to test the service. That the service was not integrated into one's everyday mobility may be related to its considerably low reliability, which was identified as an essential factor for the acceptance of such services by Etminani-Ghasrodashti et al [13].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Even for the non-users of the EVA Shuttle, the survey revealed a general open-mindedness towards the future use of an autonomous minibus. In contrast to the minibus service in Trikala (see Portouli et al [35]), but in line with most other studies, such as Rauh et al [36], the main reason for using the EVA Shuttle was to test the service. That the service was not integrated into one's everyday mobility may be related to its considerably low reliability, which was identified as an essential factor for the acceptance of such services by Etminani-Ghasrodashti et al [13].…”
Section: Discussionmentioning
confidence: 71%
“…Past and ongoing research revealed that minibuses are often used out of curiosity or technical interest. In Bad Birnbach (Germany), for example, it was shown that only 13% used the service because the bus route was suitable for their destination [36]. However, in Trikala, Greece, where an autonomous minibus was implemented as a timetable-based bus operation, people also started integrating the new service into their everyday mobility [35].…”
Section: Autonomous Minibus Servicesmentioning
confidence: 99%
“…technischem Interesse genutzt. So zeigte sich in Bad Birnbach, dass nur 13% den Dienst nutzten, weil die Strecke des Busses passend für ihr Ziel sei (Rauh et al 2020). ÖV-affine Personen haben besonders starkes Interesse an den Diensten, darüber hinaus zeigt sich Nutzungspotential darin, dass der Zugang zum ÖV vereinfacht wird (Kostorz et al 2020a).…”
Section: (Studien-)lage Der Autonomen Kleinbusseunclassified